The Recruitment and Selection process of ACI Logistics Limited (SHWAPNO) - Prachi, Zummatul Mahbin (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.